Bunching and Adjustment Costs: Evidence from Cypriot Tax Reforms - Panos Mavrokonstantis; Arthur Seibold (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study adjustment costs in behavioral responses to income taxes, exploiting tax reforms that create and subsequently eliminate income tax kinks in Cyprus. Reduced-form evidence reveals substantial adjustment frictions attenuating bunching and de-bunching responses. Combining the empirical bunching moments with a structural model of frictional earnings supply, adjustment costs are estimated between EUR 93 and EUR 238 for wage earners. Moreover, we uncover important asymmetries in adjustment frictions, where bunching at a kink is costlier than de-bunching away from the kink. Finally, we find that self-employed individuals face considerably lower adjustment costs than wage earners.
Keywords: H24; J22; 330; income taxation; taxable income responses; bunching; adjustment frictions